Integrated Approach for Development of Natural Resources in Santalpur Block of Gujarat State - Roy, B B; Gupta, R K; Pandey, S (Annals of Arid Zone, 2016)
Integrated survey of natural resources of Santalpur Panchayat Samiti block which falls in arid zone of Gujarat State was carried out to frame developmental programme for overall improvement of the economic conditions of the people. It covers an area of 1356 sq. km and gets 400 to 500 mm average annual rainfall during southwest monsoon period. The landscape of the block is almost flat with light textured soils over major part of the area. Some areas are saline. The scarcity of water is acute. Ameliorative measures have been suggested for development of water resources, agriculture, pasture, animal husbandry, etc.